Using Six Thinking-Hats to optimize the nursing process of physical examination. - ZHU Yuxia; SHI Tingting (Nursing of Integrated Traditional Chinese & Western Medicine, 2019)
Objective To evaluate the thinking model of Six Thinking-Hats in optimizing the nursing process of physical examination. Methods: The routine nursing process of physical examination was optimized by using the Six Thinking-Hats technique. The list of Traditional Chinese Medicine(TCM)constitution and syndrome differentiation was used to evaluate the first-visit subjects, and individualized physical examination was performed accordingly. The non-invasive health interventions and follow-up were carried out after the physical examination. The satisfaction degrees of patients, quality of nursing and professional self-identity of nurses were assessed. Results: After process optimization, the scores of satisfaction degree and nursing quality in 62 first-visit subjects were higher than those in 62 first-visit subjects before process optimization(P<0.01). Five nurses form the Physical Examination Center had participated in the professional self-identity assessment, and the score of Job Achievement Scale was(7.32±1.67)before process optimization and(13.77±1.98)after process optimization(P<0.01). Conclusion: It is effective to adopt Six Thinking-Hats in optimizing the nursing process of physical examination. High-quality and individualized nursing interventions based on Six Thinking Hats model can improve the nursing quality of physical examination and increase the professional self-identity of nurses.